Coupling numerical models for wave propagation in the MOIA package - Santos, João Alfredo (2020)
Sea wave action is a key factor for several aspects of port activities. Numerical models for wave forecasting at a regional level can produce quite accurate estimates of the sea state characteristics offshore a given port. There is a research project going on, code-named MOIA, that aims at developing an integrated toot to support the management of port activities by taking into account the effects of waves on some of those activities. To characterize sea waves inside a given port use is made of a set of coupled models that propagate the values that were measured or predicted off the port. The starting point is a tool developed at LNEC, SOPRO, which incorporates several of such numerical models. The paper describes the progress done so far in the coupling of the several numerical models that enable the propagation of the sea-state characteristics forecast off the Praia da Vitoria port (Terceira, Azores) up to the port terminals.